2007
DOI: 10.1007/s11033-007-9123-1
|View full text |Cite
|
Sign up to set email alerts
|

Role of IFN-γ +874 T/A single nucleotide polymorphism in the tuberculosis outcome among Brazilians subjects

Abstract: Several genetic cytokine gene variants have been associated with host susceptibility to infectious diseases, including tuberculosis. Based upon the importance of IFN-gamma in protective immunity against Mycobacterium tuberculosis, and the functional role of the IFN-gamma + 874T/A single nucleotide polymorphism in IFN-gamma production, we genotyped 93 Brazilian tuberculosis patients and 266 asymptomatic health care workers, including 150 individuals with a positive tuberculin skin test, and analyzed the possibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
24
1
2

Year Published

2008
2008
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 18 publications
7
24
1
2
Order By: Relevance
“…16,2009 CYTOKINE SNPs ASSOCIATED WITH MSF SUSCEPTIBILITY 813 chronic tuberculosis (25). This finding has been confirmed by other groups (2,35), and in a recent meta-analysis, the high IFN-␥-producing ϩ874T allele has been shown to be negatively associated with tuberculosis (31). Present data seem to confirm the protective role of a genetically determined high IFN-␥ production against bacterial infections characterized by an intracellular parasitism.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…16,2009 CYTOKINE SNPs ASSOCIATED WITH MSF SUSCEPTIBILITY 813 chronic tuberculosis (25). This finding has been confirmed by other groups (2,35), and in a recent meta-analysis, the high IFN-␥-producing ϩ874T allele has been shown to be negatively associated with tuberculosis (31). Present data seem to confirm the protective role of a genetically determined high IFN-␥ production against bacterial infections characterized by an intracellular parasitism.…”
Section: Discussionsupporting
confidence: 81%
“…In this view, our data seem to suggest that a genetic predisposition to produce high IFN-␥ levels might have a protective effect for the clinical outcome of the disease. Data from studies of intracellular infectious diseases have demonstrated that a genetically mediated reduction of the IFN-␥ response is associated with an increased susceptibility to a large arrays of pathogens (2,8,36,43). Recently, we reported, for the first time, that ϩ874T allele frequency is reduced in subjects affected by a Comparisons among the different combined genotype frequencies were performed by applying the nonparametric Mantel-Haenszel procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have been conducted in the Brazilian admixed population regarding IFN-γ polymorphisms at position +874 and its correlation, if any with infectious diseases. Amim et al (53) showed an important association in +874 AA genotype with the occurrence of active tuberculosis disease, independent of tuberculosis skin test status. However, the selection of these tuberculosis cases (from the Southwest region of Brazil) and healthy controls (from the Central-west region of Brazil) may cause a misunderstanding, because the Brazilian population is considered admixed.…”
Section: Interferon-γ γ γ γ γmentioning
confidence: 98%
“…Several factors are involved in susceptibility to active disease after infection by Mycobacterium tuberculosis including environmental and host genetic markers. Today, the search for functional genetic markers in target genes and association studies with different TB outcomes has been common in the literature (Amim et al, 2007, Calado et al, 2006. Several genes encoding different cytokines, receptors and transporters molecules are involved in the host immune response against M. tuberculosis, therefore playing crucial roles in TB susceptibility.…”
Section: Introductionmentioning
confidence: 99%